The role of open woodland in mitigating microclimatic extremes in agricultural landscapes. (30th December 2021) - Baker, Thomas P.; Marais, Zara E.; Davidson, Neil J.; Worledge, Dale; Mendham, Daniel S.
Summary: The retention of native woodland remnants in agricultural landscapes provides a range of benefits, many of which are linked to the ameliorative effects of trees on local microclimatic conditions. We monitored the reduction in wind speed and extreme temperatures that occurred in and around two native eucalypt woodland remnants in the Tasmanian Midlands and discuss the role of woodland remnants in providing both agricultural and environmental benefits. Monitoring wind speed, temperature and relative humidity every 30 min for over a year showed that an average wind speed reduction of 50% occurred within the woodland remnants as well as higher minimum temperatures by up to 0.5 C. The structural characteristics of the woodland remnants mediated the effects observed, with a 50% reduction in wind speed occurring when there was the equivalent of 20 large trees blocking the wind. This demonstrates that areas with low numbers of trees per hectare can have significant impacts on microclimatic conditions. The microclimatic changes observed will likely benefit agricultural productivity, farm aesthetics and ecological processes.